logo for solving-math-problems.com
leftimage for solving-math-problems.com

Math - Two Step Equations

by Shannon
(United States)











































to solve an equation, approach the problem using the PEMDAS order of operations “in reverse”: SADMEP

SADMEP: subtraction, addition, division, multiplication, exponents, parentheses

how to do two step equations ike this one -4+3j=-3

Comments for Math - Two Step Equations

Click here to add your own comments

Oct 21, 2011
Solve Two Step Equation
by: Staff


Question:

by Shannon
(United States)

how to do two step equations ike this one -4+3j=-3


Answer:

-4 + 3j = -3

Your goal is to place the variable “j” on one side of the equation (by itself), and everything else on the other.

To accomplish this, you must eliminate two numbers from the left side of the equation: a) the -4, and b) the 3.

The question is: how do you accomplish this?

You approach the problem using the PEMDAS order of operations “in reverse”: SADMEP

PEMDAS: parentheses, exponents, multiplication, division, addition, subtraction

SADMEP: subtraction, addition, division, multiplication, exponents, parentheses


You can rearrange the terms on the left side of the equation to make the format look a little more familiar:

-4 + 3j = -3

3j - 4 = -3


The 1st step is to remove what you can using S (subtraction) or A (addition).

This means you should eliminate the “-4” first.

What is the opposite of -4? It is +4.

When you add 4 to each side of the equation, the -4 on the left side of the equation disappears.

-4 + 4 = 0

3j - 4 + 4 = -3 + 4

3j + 0 = -3 + 4

3j = -3 + 4

3j = 4 – 3

3j = 1


The 2nd step is to remove the 3 from the left side of the equation.

What is the opposite of 3 * j? It is j ÷ 3.

When you divide each side of the equation by 3, the 3 on the left side of the equation disappears.

3 * j / 3 = j * (3 / 3) = j


3j = 1

3j / 3 = 1 / 3

j * (3 / 3) = 1 / 3

j * (1) = 1 / 3

j = 1 / 3


the final answer is: j = 1/3



Check your work. Substitute 1/3 for the variable j in the original equation.

-4 + 3j = -3

-4 + 3 * 1/3 = -3

-4 + 1 * (3 / 3) = -3

-4 + 1 * (1) = -3

-4 + 1 = -3

-3 = -3→ j = 1/3 is a valid solution




Thanks for writing.

Staff
www.solving-math-problems.com



Click here to add your own comments

Join in and write your own page! It's easy to do. How? Simply click here to return to Math Questions & Comments - 01.



Copyright © 2008-2015. All rights reserved. Solving-Math-Problems.com